Feasibility and Practicality of Interactive E-Modules on Respiratory System Materials - Hasibuan, Fitria Ulfa; M, Marjanah; Armanda, Fahmy (JIPVA (Jurnal Pendidikan IPA Veteran), 2024)
This study aims to determine the feasibility and practicality of the interactive e-modules produced. This study uses a research and development (R&D) method with a 4-D development model (Thiagarajan), namely define, design, develop, and disseminate which is limited to the development stage . The validity of the e-module is measured based on the validation of material experts, media experts, and linguists. The practicality of the e-module is measured based on the results of teacher and student responses. The research was piloted on a limited basis on 19 students in grade XI MIA 1 MAN 1 Langsa. The results of the interactive e-module research on respiratory system material received a feasibility assessment from material experts of 98%, from media experts of 94%, and from linguists of 96% with the criteria of "very feasible". Meanwhile, the assessment of practicality from the teacher's response was 96.6%, and the student's response was 92.2% with the criterion of "very practical". Based on these results, it can be concluded that the interactive e-module on the respiratory system material developed is feasible and practical to be used in the learning process.